Influence of the psychical well-being on the basis of the requisite personal holism of employees on effectiveness of the organization and the way out from the current crisis - Šarotar Žižek, Simona; Treven, Sonja; Mulej, Matjaž (Anali PAZU HD, 2022)
The contemporary world is in a deep crisis. The way out from it depends on personal requisite holism. Therefore, along with the organization (including its effectiveness and HRM) the core of this research is the human as employee having capabilities, knowledge, skills and personal attributes and marked with motivation, will, values and other emotions. On this base the human tries to realize one’s personal sense of life, including one’s role of an employee. Although one’s work gives to the human one’s identity, self-respect, social support and material rewards, one’s work is not one’s only role in one’s life; one’s roles as a partner, parent, relative, friend, neighbor matter equally. Every role causes also duties to be realized as optimally as possible in line with the established social norms.